EDUKASI BAHAYA KONSUMSI GARAM BERLEBIHAN PADA ANAK MELALUI DEMONSTRASI INTERAKTIF MEDIA AIR DAN GARAM - Dwi Evi Diyan Sari; Faizatul Fitria; Erni Anikasari; Krisogonus Ephrino Seran; Yogi Bhakti Marhenta; Eko Yudha Prasetyo (Jurnal AbdiMas Nusa Mandiri, 2026)
Excessive salt consumption from an early age can shape a lasting preference for salty foods that persists into adulthood and may increase the risk of health problems later in life. This community service activity aimed to improve young children's understanding of the dangers of excessive salt consumption through an interactive demonstration method based on learning by doing. The activity employed an interactive educational approach using demonstrations of salt solutions with different concentrations involving 30 preschool children from KB and TK Al Munawaroh at Bhakta Health Park in April 2026. Evaluation was conducted using simple visual-based pre-tests and post-tests, as well as observations and educational games. Data were analyzed descriptively and quantitatively by comparing pre-test and post-test scores. The results showed improvements in participants' understanding across all indicators. The ability to recognize healthy foods increased from 40% to 90%, understanding of the dangers of excessive salt consumption increased from 30% to 80%, and the ability to visually identify different salt concentration levels increased from 0% to 70%. All indicators met the program's success criterion, with at least 70% of participants answering correctly in the post-test. The findings indicate that the interactive demonstration method is effective in improving young children's understanding of healthy salt consumption and can serve as an alternative health education strategy from an early age.